Investigating Register Variation On Coronavirus Disease (Covid-19) Posts In Social Media - Epsulaili, Septia (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with the study of register variation on social media posts about corona virus disease (Covid-19). The aim of this research is to investigate the types of register on social media posts specifically around covid-19 issues and to investigate the realization of register term in social media posts such as Instagram and twitter about covid-19 outbreak. The research is applied descriptive qualitative method. The data of this research is the text posts on social media that were taken through screenshot the posts identified register and notetaking. There 50 register terms found that were analyzed based on Miles and Huberman, including data reduction data display, and conclusion. Based on analysis, the research finding showed that register is realized based on Field, Tenor and Mode as the types of register. There are six function of register but the finding showed that realization of register on social media posts provided two functions such as information function and interaction function. The register terms are realized through monolingual (Bahasa) and Bilingual (Bahasa and English).